Metal ion doped lithium hexafluorosilicate and preparation method thereof, negative plate and preparation method thereof, and lithium ion battery
Metal ion-doped lithium hexafluorosilicate forms a double-layer SEI film on the negative electrode sheet, addressing stability and fast charging limitations in lithium-ion batteries by enhancing interlayer spacing and pore structure, thereby improving cycle stability and fast charging performance.
Patent Information
- Application Number
- CN202411746366.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-12-02
AI Technical Summary
Existing lithium-ion batteries face limitations in cycle stability and fast charging capability due to the formation of a stable SEI film, which is not optimized for rapid lithium ion transmission and dendrite formation prevention.
A metal ion-doped lithium hexafluorosilicate (Li 2-x A x SiF6) is used to pre-form a SEI film on the negative electrode sheet, enhancing interlayer spacing and pore structure, forming a double-layer SEI film that improves lithium desolvation and inhibits dendrite formation.
The solution significantly enhances the cycle stability and fast charging capability of lithium-ion batteries by improving lithium ion transmission and preventing dendrite formation, resulting in high energy density, long cycle life, and excellent fast charging performance.
Smart Images

Figure CN119252924A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ion batteries, and in particular to metal ion-doped lithium hexafluorosilicate and a preparation method thereof, a negative electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art
[0002] During the first charge and discharge process of lithium-ion batteries, the electrode material will react with the electrolyte at the solid-liquid interface to form a SEI film covering the surface of the electrode material. The stable SEI film can effectively prevent solvent molecules from damaging the electrode material, thereby improving the cycle stability and service life of lithium-ion batteries. Summary of the invention
[0003] Based on this, it is necessary to provide a metal ion-doped lithium hexafluorosilicate and a preparation method thereof, a negative electrode sheet and a preparation method thereof, and a lithium ion battery to address the above problems. The metal ion-doped lithium hexafluorosilicate is used to pre-form a SEI film on the surface of the negative electrode sheet, which can effectively improve the cycle stability and service life of the lithium ion battery, and can also improve the fast charging capability of the lithium ion battery.
[0004] A metal ion doped lithium hexafluorosilicate, wherein the chemical formula of the metal ion doped lithium hexafluorosilicate is Li 2- x A x SiF6, wherein A is a first main group metal and does not include Li, and x is 0.5-1.5.
[0005] In one embodiment, A is selected from at least one of Na and K.
[0006] A method for preparing metal ion-doped lithium hexafluorosilicate comprises the following steps: Li2SiF6 and A2SiF6 are placed in an organic solvent and Li is obtained by proton transfer reaction. 2-x A x SiF6, wherein A is a first main group metal and x is 0.5-1.5.
[0007] In one embodiment, SiO2 and LiPF6 are placed in an organic solvent and Li2SiF6 is prepared by a proton transfer reaction.
[0008] In one embodiment, the SiO2 has a porous spherical morphology.
[0009] A negative electrode sheet, comprising a current collector and an active material layer attached to the surface of the current collector, wherein the surface of the active material layer is also attached with a Li 2-x A x SEI film made of SiF6.
[0010] In one embodiment, the negative electrode active material in the active material layer is selected from graphite.
[0011] A method for preparing the negative electrode sheet comprises the following steps: Providing a prefabricated negative electrode sheet, the prefabricated negative electrode sheet comprising a current collector and an active material layer attached to a surface of the current collector; Li 2-x A x SiF6 and a binder are placed in an organic solvent to obtain a dispersion, the dispersion is placed on the surface of the active material layer of the prefabricated negative electrode sheet, and the negative electrode sheet is obtained after drying.
[0012] In one embodiment, the dispersion contains Li 2-x A x The concentration of SiF6 is 12 mg / mL-18 mg / mL, and based on the prefabricated negative electrode sheet with a diameter of 12 mm, the amount of the dispersion used is 5 μL-10 μL.
[0013] A lithium-ion battery, characterized by comprising the negative electrode sheet.
[0014] Compared with Li2SiF6, the present invention uses the first main group metal ions with larger ionic radius to replace part of Li + Li 2-x A x SiF6 has a larger interlayer spacing and a richer pore structure. 2-x A x SiF6 pre-forms a SEI film on the surface of the negative electrode. During the cycle, the rich pore structure and larger interlayer spacing can better improve the Li + The desolvation ability of Li + The double-layer SEI film can transmit and induce uniform lithium deposition to form an inorganic-rich SEI film between the SEI film and the active material layer, further inhibiting the formation of lithium dendrites and improving the cycle stability and service life of lithium-ion batteries. At the same time, the double-layer SEI film significantly improves the stability and capacity of the negative electrode during fast charging, providing strong support for the fast charging of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the conventional technology, the drawings required for use in the embodiments or the conventional technology descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0016] Figure 1This is a scanning electron microscope image of LiNaSiF6 prepared in Example 3 of the present invention; Figure 2 XRD diagrams of Li2SiF6 prepared in Comparative Example 2 of the present invention and LiNaSiF6 prepared in Example 3. DETAILED DESCRIPTION
[0017] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0019] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0020] The inherent pore structure and gap size of Li2SiF6 make it limited in improving the performance of electrode sheets and coping with mechanical strain. Therefore, the present invention provides a metal ion doped lithium hexafluorosilicate, the chemical formula of the metal ion doped lithium hexafluorosilicate is Li 2-x A x SiF6, wherein A is a first main group metal and does not include Li. Since the ionic radius of metal ion A is larger than the ionic radius of Li, metal ion A is used to replace part of Li in Li2SiF6. + After that, the interlayer spacing can be widened and the pores can be increased, making Li 2-x A x SiF6 has a larger interlayer spacing and a richer pore structure than Li2SiF6. Preferably, A is selected from at least one of Na and K.
[0021] Since the amount of metal ion doping has a significant effect on its lattice spacing, x is controlled in the range of 0.5-1.5, for example, x is 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4 or 1.5, and more preferably 0.8-1.1.
[0022] The present invention also provides a method for preparing the metal ion-doped lithium hexafluorosilicate, comprising the following steps: Li2SiF6 and A2SiF6 are placed in an organic solvent and Li is obtained by proton transfer reaction. 2-x A x SiF6, wherein A is a first main group metal and x is 0.5-1.5.
[0023] The preparation method of the present invention has no requirements on the preparation method and source of Li2SiF6. SiO2 has a high specific surface area, good thermal conductivity and stability. After Li2SiF6 is synthesized by SiO2, it is doped with metal ions A to obtain Li 2-x A x SiF6 has a richer pore structure and a larger interlayer spacing. Therefore, the present invention preferably places SiO2 and LiPF6 in an organic solvent, uses a proton transfer reaction to prepare Li2SiF6, and then performs a proton transfer reaction between Li2SiF6 and A2SiF6 to prepare Li 2-x A x SiF6, wherein the morphology of the SiO2 is further preferably a porous sphere, having a richer pore structure and a larger specific surface area, and having a better effect. When SiO2 and LiPF6 are placed in an organic solvent for a proton transfer reaction, LiPF6 is in excess to allow the SiO2 to react completely.
[0024] Li 2-x A x In SiF6, A is preferably at least one of Na and K, so A2SiF6 is preferably at least one of Na2SiF6 and K2SiF6. In addition, Li2SiF6 and A2SiF6 are subjected to proton transfer reaction to prepare Li 2-x A x When SiF6 is used, the amount of A2SiF6 can be calculated based on the choice of metal ion A and the required doping amount x.
[0025] The proton transfer reaction between SiO2 and LiPF6 to prepare Li2SiF6 and the proton transfer reaction between Li2SiF6 and A2SiF6 to prepare Li 2-x A xIn the SiF6 step, the organic solvent used can be selected from acetonitrile and the like, and there is no special requirement.
[0026] The present invention also provides a negative electrode sheet, comprising a current collector and an active material layer attached to the surface of the current collector, wherein the surface of the active material layer is also attached with the Li 2-x A x SEI film made of SiF6. Among them, the active material layer is made of negative electrode active material, binder, conductive agent, etc. in proportion.
[0027] The present invention adopts Li 2-x A x SiF6 preforms a SEI film on the surface of the negative electrode. After the negative electrode is assembled into a lithium-ion battery, the rich pore structure and larger interlayer spacing of the preformed SEI film can better improve the Li + The desolvation ability of Li + The inorganic-rich SEI film is generated between the SEI film and the active material layer after inducing the uniform deposition of lithium, further inhibiting the formation of lithium dendrites and improving the cycle stability and service life of lithium-ion batteries. At the same time, the induced inorganic-rich SEI film and the pre-formed SEI film form a double-layer SEI film, which significantly improves the stability and capacity of the negative electrode during fast charging, providing strong support for the fast charging of lithium-ion batteries.
[0028] Graphite negative electrode sheets dominate the negative electrode sheets of lithium-ion batteries due to their high energy density, low cost and long cycle life. However, due to the layered structure of graphite itself and the solvation of lithium ions, the ion transmission rate of the graphite negative electrode sheet is slow, and the fast charging capacity of the entire lithium-ion battery is limited. The inorganic-rich SEI film induced by the present invention and the pre-formed SEI film constitute a double-layer SEI film, which significantly improves the stability and capacity of the negative electrode sheet during fast charging. Therefore, the negative electrode active material in the active material layer of the present invention is selected from graphite, and Li 2-x A x SiF6 pre-forms a SEI film on the surface of the negative electrode, which can make the lithium-ion battery have high energy density, low cost, long cycle life and excellent fast charging capability.
[0029] The present invention also provides a method for preparing the negative electrode sheet, comprising the following steps: Providing a prefabricated negative electrode sheet, the prefabricated negative electrode sheet comprising a current collector and an active material layer attached to a surface of the current collector; Li 2-x A xSiF6 and a binder are placed in an organic solvent to obtain a dispersion, the dispersion is placed on the surface of the active material layer of the prefabricated negative electrode sheet, and the negative electrode sheet is obtained after drying.
[0030] It can be understood that the prefabricated negative electrode sheet is a traditional negative electrode sheet, which is obtained by mixing the negative electrode active material, the conductive agent and the binder to form a slurry, coating the slurry on the current collector, drying and slicing. The present invention is mainly based on the traditional negative electrode sheet, and then using Li 2-x A x SiF6 pre-forms a SEI film on the surface of the negative electrode.
[0031] Optionally, Li 2-x A x In the step of placing SiF6 and a binder in an organic solvent to obtain a dispersion, the organic solvent is selected from N,N-dimethylformamide (DMF) and the like, the binder is selected from sodium carboxymethyl cellulose (CMC-Na), polyvinylidene fluoride (PVDF) and the like, and the Li 2-x A x The concentration of SiF6 is preferably 12 mg / mL-18 mg / mL. Taking the prefabricated negative electrode sheet with a diameter of 12 mm as a reference, the amount of the dispersion is 5 μL-10 μL. The dispersion can be placed on the surface of the active material layer of the prefabricated negative electrode sheet by coating, dripping, etc.
[0032] The present invention also provides a lithium ion battery, wherein the lithium ion battery uses the negative electrode sheet.
[0033] Hereinafter, the metal ion-doped lithium hexafluorosilicate and its preparation method, the negative electrode sheet and its preparation method, and the lithium ion battery will be further described through the following specific examples.
[0034] Comparative Example 1 Weigh 320 mg of artificial graphite material, 40 mg of conductive carbon black and 40 mg of carboxymethyl cellulose, add appropriate amount of deionized water and use planetary ball mill for 2 h, coat the milled slurry on copper foil, and cut it into graphite negative electrode sheets with a diameter of 12 mm after vacuum drying at 80 ° C for 12 h. The loading is 2.5 mg / cm 2 .
[0035] Comparative Example 2 In a glove box, 500 mg of porous spherical SiO2 powder and 1.5 g of LiPF6 powder were weighed, and then 10 mL of acetonitrile solution was added and magnetically stirred for 24 h to obtain a Li2SiF6 suspension through a proton transfer reaction. The obtained suspension was centrifuged several times with acetonitrile in the glove box to wash away the residual LiPF6, and then dried in the glove box to obtain Li2SiF6 powder.
[0036] Weigh 100 mg of PVDF powder, add 20 mL of DMF solution, stir magnetically for a period of time to make it a homogeneous solution, then disperse the Li2SiF6 material obtained by the above centrifugation into the homogeneous solution, shake it to make it evenly dispersed, and obtain a dispersion, wherein the concentration of Li2SiF6 material in the dispersion is 15 mg / mL.
[0037] 10 μL of the above dispersion was evenly dripped on the surface of the graphite negative electrode sheet of Comparative Example 1, and then dried at 80° C. for 20 min to obtain a negative electrode sheet with a SEI film on the surface.
[0038] Comparative Example 3 In a glove box, 500 mg of porous spherical SiO2 powder and 1.5 g of LiPF6 powder were weighed, and then 10 mL of acetonitrile solution was added and magnetically stirred for 24 h to obtain a Li2SiF6 suspension through a proton transfer reaction. The obtained suspension was centrifuged several times with acetonitrile in the glove box to wash away the residual LiPF6, and then dried in the glove box to obtain Li2SiF6 powder.
[0039] Weigh 500 mg of the above-obtained Li2SiF6 powder and 90 mg of Na2SiF6 and dissolve them in 10 mL of acetonitrile solution and stir them magnetically for 24 h to obtain Li 1.7 Na 0.3 The suspension of SiF6 was centrifuged several times with acetonitrile in a glove box to obtain Li 1.7 Na 0.3 SiF6 material.
[0040] Weigh 100 mg of PVDF powder, add 20 mL of DMF solution, stir magnetically for a while to make it a homogeneous solution, and then add the Li 1.7 Na 0.3 SiF6 material is dispersed into a homogeneous solution and shaken to make it evenly dispersed to obtain a dispersion, wherein Li 1.7 Na 0.3 The concentration of SiF6 material was 16 mg / mL.
[0041] 10 μL of the above dispersion was evenly dripped on the surface of the graphite negative electrode sheet of Comparative Example 1, and then dried at 80° C. for 20 min to obtain a negative electrode sheet with a SEI film on the surface.
[0042] Comparative Example 4 In a glove box, 500 mg of porous spherical SiO2 powder and 1.5 g of LiPF6 powder were weighed, and then 10 mL of acetonitrile solution was added and magnetically stirred for 24 h to obtain a Li2SiF6 suspension through a proton transfer reaction. The obtained suspension was centrifuged several times with acetonitrile in the glove box to wash away the residual LiPF6, and then dried in the glove box to obtain Li2SiF6 powder.
[0043] Weigh 500 mg of the above-obtained Li2SiF6 powder and 540 mg of Na2SiF6 and dissolve them in 10 mL of acetonitrile solution and stir them magnetically for 24 h to obtain Li 0.2 Na 1.8 The suspension of SiF6 was centrifuged several times with acetonitrile in a glove box to obtain Li 0.2 Na 1.8 SiF6 material.
[0044] Weigh 100 mg of PVDF powder, add 20 mL of DMF solution, stir magnetically for a while to make it a homogeneous solution, and then add the Li 0.2 Na 1.8 SiF6 material is dispersed into a homogeneous solution and shaken to make it evenly dispersed to obtain a dispersion, wherein Li 0.2 Na 1.8 The concentration of SiF6 material was 17 mg / mL.
[0045] 10 μL of the above dispersion was evenly dripped on the surface of the graphite negative electrode sheet of Comparative Example 1, and then dried at 80° C. for 20 min to obtain a negative electrode sheet with a SEI film on the surface.
[0046] Example 1 In a glove box, 500 mg of porous spherical SiO2 powder and 1.5 g of LiPF6 powder were weighed, and then 10 mL of acetonitrile solution was added and magnetically stirred for 24 h to obtain a Li2SiF6 suspension through a proton transfer reaction. The obtained suspension was centrifuged several times with acetonitrile in the glove box to wash away the residual LiPF6, and then dried in the glove box to obtain Li2SiF6 powder.
[0047] Weigh 500 mg of the above-obtained Li2SiF6 powder and 150 mg of Na2SiF6 and dissolve them in 10 mL of acetonitrile solution and stir them magnetically for 24 h to obtain Li 1.5 Na 0.5 The suspension of SiF6 was centrifuged several times with acetonitrile in a glove box to obtain Li 1.5 Na 0.5 SiF6 material.
[0048] Weigh 100 mg of PVDF powder, add 20 mL of DMF solution, stir magnetically for a while to make it a homogeneous solution, and then add the Li 1.5 Na 0.5 SiF6 material is dispersed into a homogeneous solution and shaken to make it evenly dispersed to obtain a dispersion, wherein Li 1.5 Na 0.5 The concentration of SiF6 material was 15 mg / mL.
[0049] 10 μL of the above dispersion was evenly dripped on the surface of the graphite negative electrode sheet of Comparative Example 1, and then dried at 80° C. for 20 min to obtain a negative electrode sheet with a SEI film on the surface.
[0050] Example 2 In a glove box, 500 mg of porous spherical SiO2 powder and 1.5 g of LiPF6 powder were weighed, and then 10 mL of acetonitrile solution was added and magnetically stirred for 24 h to obtain a Li2SiF6 suspension through a proton transfer reaction. The obtained suspension was centrifuged several times with acetonitrile in the glove box to wash away the residual LiPF6, and then dried in the glove box to obtain Li2SiF6 powder.
[0051] Weigh 500 mg of the above-obtained Li2SiF6 powder and 180 mg of K2SiF6 and dissolve them in 10 mL of acetonitrile solution and stir them magnetically for 24 h to obtain Li 1.5 K 0.5 The suspension of SiF6 was centrifuged several times with acetonitrile in a glove box to obtain Li 1.5 K 0.5 SiF6 material.
[0052] Weigh 100 mg of PVDF powder, add 20 mL of DMF solution, stir magnetically for a while to make it a homogeneous solution, and then add the Li 1.5 K 0.5 SiF6 material is dispersed into a homogeneous solution and shaken to make it evenly dispersed to obtain a dispersion, wherein Li 1.5 K 0.5 The concentration of SiF6 material was 16 mg / mL.
[0053] 10 μL of the above dispersion was evenly dripped on the surface of the graphite negative electrode sheet of Comparative Example 1, and then dried at 80° C. for 20 min to obtain a negative electrode sheet with a SEI film on the surface.
[0054] Example 3 In a glove box, 500 mg of porous spherical SiO2 powder and 1.5 g of LiPF6 powder were weighed, and then 10 mL of acetonitrile solution was added and magnetically stirred for 24 h to obtain a Li2SiF6 suspension through a proton transfer reaction. The obtained suspension was centrifuged several times with acetonitrile in the glove box to wash away the residual LiPF6, and then dried in the glove box to obtain Li2SiF6 powder.
[0055] Weigh 500 mg of the above-obtained Li2SiF6 powder and 300 mg of Na2SiF6 and dissolve them in 10 mL of acetonitrile solution and stir them magnetically for 24 h to obtain a suspension of LiNaSiF6 by proton transfer reaction. The obtained suspension is centrifuged several times with acetonitrile in a glove box to obtain Figure 1 The LiNaSiF6 material shown. Figure 2 As shown, A is the XRD curve of the LiNaSiF6 material obtained in this embodiment, and B is the XRD curve of the Li2SiF6 material obtained in Comparative Example 2. Figure 2 It can be seen that the peak of the LiNaSiF6 material obtained by Na ion doping shifts to the left, indicating that the lattice spacing of the material becomes larger and the doping is successful.
[0056] Weigh 100 mg of PVDF powder, add 20 mL of DMF solution, stir magnetically for a period of time to make it a homogeneous solution, then disperse the LiNaSiF6 material obtained by the above centrifugation into the homogeneous solution, shake it to make it evenly dispersed, and obtain a dispersion, wherein the concentration of the LiNaSiF6 material in the dispersion is 16 mg / mL.
[0057] 10 μL of the above dispersion was evenly dripped on the surface of the graphite negative electrode sheet of Comparative Example 1, and then dried at 80° C. for 20 min to obtain a negative electrode sheet with a SEI film on the surface.
[0058] Example 4 In a glove box, 500 mg of porous spherical SiO2 powder and 1.5 g of LiPF6 powder were weighed, and then 10 mL of acetonitrile solution was added and magnetically stirred for 24 h to obtain a Li2SiF6 suspension through a proton transfer reaction. The obtained suspension was centrifuged several times with acetonitrile in the glove box to wash away the residual LiPF6, and then dried in the glove box to obtain Li2SiF6 powder.
[0059] 500 mg of the above-obtained Li2SiF6 powder and 350 mg of K2SiF6 were weighed and dissolved in 10 mL of acetonitrile solution and magnetically stirred for 24 h to obtain a LiKSiF6 suspension through a proton transfer reaction. The obtained suspension was centrifuged several times with acetonitrile in a glove box to obtain a LiKSiF6 material.
[0060] Weigh 100 mg of PVDF powder, add 20 mL of DMF solution, stir magnetically for a period of time to make it a homogeneous solution, then disperse the LiKSiF6 material obtained by the above centrifugation into the homogeneous solution, shake it to make it evenly dispersed, and obtain a dispersion, wherein the concentration of LiKSiF6 material in the dispersion is 16 mg / mL.
[0061] 10 μL of the above dispersion was evenly dripped on the surface of the graphite negative electrode sheet of Comparative Example 1, and then dried at 80° C. for 20 min to obtain a negative electrode sheet with a SEI film on the surface.
[0062] Example 5 In a glove box, 500 mg of porous spherical SiO2 powder and 1.5 g of LiPF6 powder were weighed, and then 10 mL of acetonitrile solution was added and magnetically stirred for 24 h to obtain a Li2SiF6 suspension through a proton transfer reaction. The obtained suspension was centrifuged several times with acetonitrile in the glove box to wash away the residual LiPF6, and then dried in the glove box to obtain Li2SiF6 powder.
[0063] Weigh 500 mg of the above-obtained Li2SiF6 powder and 450 mg of Na2SiF6 and dissolve them in 10 mL of acetonitrile solution and stir them magnetically for 24 h to obtain Li 0.5 Na 1.5 The suspension of SiF6 was centrifuged several times with acetonitrile in a glove box to obtain Li 0.5 Na 1.5 SiF6 material.
[0064] Weigh 100 mg of PVDF powder, add 20 mL of DMF solution, stir magnetically for a while to make it a homogeneous solution, and then add the Li 0.5 Na 1.5 SiF6 material is dispersed into a homogeneous solution and shaken to make it evenly dispersed to obtain a dispersion, wherein Li 0.5 Na 1.5 The concentration of SiF6 material was 17 mg / mL.
[0065] 10 μL of the above dispersion was evenly dripped on the surface of the graphite negative electrode sheet of Comparative Example 1, and then dried at 80° C. for 20 min to obtain a negative electrode sheet with a SEI film on the surface.
[0066] Example 6 In a glove box, 500 mg of porous spherical SiO2 powder and 1.5 g of LiPF6 powder were weighed, and then 10 mL of acetonitrile solution was added and magnetically stirred for 24 h to obtain a Li2SiF6 suspension through a proton transfer reaction. The obtained suspension was centrifuged several times with acetonitrile in the glove box to wash away the residual LiPF6, and then dried in the glove box to obtain Li2SiF6 powder.
[0067] Weigh 500 mg of the above-obtained Li2SiF6 powder and 530 mg of K2SiF6 and dissolve them in 10 mL of acetonitrile solution and stir them magnetically for 24 h to obtain Li 0.5 K 1.5 The suspension of SiF6 was centrifuged several times with acetonitrile in a glove box to obtain Li 0.5 K 1.5 SiF6 material.
[0068] Weigh 100 mg of PVDF powder, add 20 mL of DMF solution, stir magnetically for a while to make it a homogeneous solution, and then add the Li 0.5 K 1.5 SiF6 material is dispersed into a homogeneous solution and shaken to make it evenly dispersed to obtain a dispersion, wherein Li 0.5 K 1.5 The concentration of SiF6 material was 17 mg / mL.
[0069] 10 μL of the above dispersion was evenly dripped on the surface of the graphite negative electrode sheet of Comparative Example 1, and then dried at 80° C. for 20 min to obtain a negative electrode sheet with a SEI film on the surface.
[0070] The negative electrode sheets of the embodiments and comparative examples were used, metallic lithium was used as the counter electrode and the reference electrode, a PP membrane was selected as the diaphragm, LiPF6 with a concentration of 1 mol / L was used as the electrolyte, and the solvent was a mixed solution of diethyl carbonate and ethylene carbonate with a volume ratio of 1:1. The button cells were assembled in a glove box with an argon atmosphere, and the electrochemical performance of the obtained button cells was tested at room temperature of 30°C and a current density of 2C. The results are shown in Table 1.
[0071] Table 1 As can be seen from Table 1, after doping with metal ions A and controlling the doping amount x within 0.5-1.5, the cycle stability, service life and fast charging capability of lithium-ion batteries can be effectively improved. In addition, as can be seen from Table 1, after doping with Na ions and controlling the atomic ratio with Li ions at about 1:1, the performance is the best. At a low current density of 0.2C, the first efficiency can reach 92.12%, and at a larger current density of 2C, it can still maintain 366.28 mAh g after 100 cycles. -1 It has high specific capacity, excellent cycle stability and rate performance, and good fast charging performance.
[0072] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0073] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A metal ion-doped lithium hexafluorosilicate, characterized in that: The chemical formula of the metal ion doped lithium hexafluorosilicate is Li 2-x A x SiF6, wherein A is a first main group metal and does not include Li, and x is 0.5-1.
5.
2. The metal ion-doped lithium hexafluorosilicate according to claim 1, characterized in that: A is selected from at least one of Na and K.
3. A method for preparing metal ion-doped lithium hexafluorosilicate as claimed in claim 1 or claim 2, characterized in that: The following steps are involved: Li2SiF6 and A2SiF6 are placed in an organic solvent and Li is obtained by proton transfer reaction. 2-x A x SiF6, wherein A is a first main group metal and x is 0.5-1.
5.
4. The method for preparing metal ion-doped lithium hexafluorosilicate according to claim 3, characterized in that: SiO2 and LiPF6 are placed in an organic solvent and Li2SiF6 is prepared by proton transfer reaction.
5. The method for preparing metal ion-doped lithium hexafluorosilicate according to claim 4, characterized in that: The SiO2 has a porous spherical shape.
6. A negative electrode sheet, characterized in that: The invention comprises a current collector and an active material layer attached to the surface of the current collector, wherein the surface of the active material layer is further attached with the Li according to claim 1 or claim 2 2-x A x SEI film made of SiF6.
7. The negative electrode sheet according to claim 6, characterized in that: The negative electrode active material in the active material layer is selected from graphite.
8. A method for preparing a negative electrode sheet according to claim 6 or claim 7, characterized in that: The following steps are involved: Providing a prefabricated negative electrode sheet, the prefabricated negative electrode sheet comprising a current collector and an active material layer attached to a surface of the current collector; Li 2-x A x SiF6 and a binder are placed in an organic solvent to obtain a dispersion, the dispersion is placed on the surface of the active material layer of the prefabricated negative electrode sheet, and the negative electrode sheet is obtained after drying.
9. The method for preparing a negative electrode sheet according to claim 8, characterized in that: The dispersion contains Li 2-x A x The concentration of SiF6 is 12 mg / mL-18 mg / mL, and based on a prefabricated negative electrode sheet with a diameter of 12 mm, the amount of the dispersion used is 5 μL-10 μL.
10. A lithium ion battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 6 or claim 7.
Citation Information
Patent Citations
Anode active material for lithium storage battery and lithium storage battery having the same
CN101872861A
High-rate high-safety soft package lithium-ion battery and preparation method thereof
CN106450433A
Graphite negative electrode structure combination and preparation method thereof, and lithium battery cell
CN108365167A
Manganese-doped phosphor materials for high power density applications
CN109072075A
Pre-lithiation method for lithium ion battery
CN109713227A
Cited By
Solid electrolyte and production method for same, electrochemical cell, battery, and oxygen supply device
WO2026150903A1